Analysis of currents on the continental shelf off the Santa Catarina Island through measured data - Dalbosco,Anna Luiza Pacheco (2020)
ABSTRACT The coastal currents and forcing agents that conduct them are still little-known in the internal continental shelf of Santa Catarina. Therefore, this work aimed to analyze the data of currents measured off the Island of Santa Catarina in order to better comprehend its patterns and forcing agents. The three measuring stations were installed in shallow water near the Arvoredo Biological Marine Reserve (ST01), Jurerê Beach (ST02) and Ingleses Beach (ST03). Data were collected by a current meter from January 22, 2014 to December 17, 2014. In the consisted data set, it was performed a basic statistical analysis, spectral decomposition and harmonic analysis in the tide components. All the stations presented a resulting southward flow, especially the station next to Arvoredo Marine Biological Reserve (ST01). The meteorological forcing has a strong contribution to the magnitude and direction of component v (alongshore). While the tidal component has greater importance in the cross-shore flow (component u). The wind showed a strong correlation with currents and the local level, indicating to be the main forcing agent of the flow in the subtidal frequency.